Design of a pure sine wave inverter for PV application - Sayeed, Nuzhat Noor; Hossain, Ahmed Aaqib Sajjad; Hasan, Nazmul; Bhuiyan, Menhajul Abedin (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.